Acquired Neuromuscular Disorders Pathogenesis, Diagnosis and Treatment - Angelini, Corrado (Springer International Publishing : Imprint: Springer, 2016)
This book provides state of the art information on the pathogenesis, diagnosis, and treatment of a range of inflammatory, autoimmune, and idiopathic neuromuscular disorders. The opening section discusses the differential diagnosis of acquired myopathies based on clinical, electrophysiological, muscle biopsy, and serological criteria, with special focus on the role of electromyography and antibody testing. Each of the relevant clinical entities is then discussed in detail, the coverage including, for example, myasthenia gravis, polymyositis, immune-mediated neuropathies, multifocal motor neuropathies, amyotrophic lateral sclerosis, paraneoplastic neuropathies, and diabetic polyneuropathy. Clear guidance is provided on currently available treatments, with descriptions of the latest advances in physiotherapy, drug therapy, and respiratory care. Other features of this clinically oriented book are the inclusion of many illustrative case presentations and contributions by international authors from leading centers.